Margaret Thatcher on leadership : lessons for American conservatives today - Gardiner, Nile; Thompson, Stephen, (Writer on British history) (Washington, DC : Regnery Publishing, Inc., an Eagle Publishing Company, 2013)
A guide for conservatives that combines stories from Thatcher's life with principles and strategies they can apply to their challenges today, including articulating conservative principles to a broader audience, cutting through bureaucracy to achieve goals, and standing up to opposition.
Includes bibliographical references and index.
Keywords: Thatcher, Margaret; Thatcher, Margaret -- Political and social views; Thatcher, Margaret; Conservative Party (Great Britain) -- Biography; Conservative Party (Great Britain); Prime ministers -- Great Britain -- Biography; Women -- Political activity -- Great Britain; Conservatism -- United States; Conservatism; Political and social views; Prime ministers; Women -- Political activity; Great Britain; United States; Biography